KAMPOENG KITE: INKUBATOR BERBASIS KEBUDAYAAN BETAWI - Ronald Leonardo; Maria Veronica Gandha (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
In the city of Jakarta, there are tribes that can be said to be quite popular, namely the Betawi tribe, but in practice Betawi is only applied as general knowledge, which is taught in the media and educational institutions. Without us knowing and interpreting what it means and what is behind what is said to be Betawi. In reality, the Betawi tribe as a local ethnic group is often narrated as a marginal, less intellectual, lower middle class economy and other negative stereotypes circulating in a multicultural society. Using the typology method in the design, to change and create new perceptions and narratives about Betawi. Adapting from the perspective of architecture, customs, and also the daily life of Betawi customs, then translated into a form and space that is different but contains the same elements. Transforming a new form of Betawi traditional house, by reconstructing every related element, from the aspect of structure, ornament, philosophy, etc.This project aims to change the stereotypes/views of people towards Betawi and create a new paradigm and stigma against the Betawi community. By raising the real problems faced, namely the economy and also the identity crisis, it is promoted to design facilities that can accommodate productivity and on the other hand promote Betawi culture itself. Keywords:  Betawi; Typology; Stereotypes; Community. AbstrakKota Jakarta terdapat suku yang dapat dikatakan cukup populer yaitu suku Betawi, tetapi secara praktik Betawi hanya diterapkan sebagai pengetahuan umum saja, yang diajarkan di media dan institusi pendidikan. Tanpa kita tahu dan memaknai apa arti dan apa yang ada dibalik yang dikatakan sebagai Betawi. Pada kenyataan yang terjadi suku Betawi sebagai etnis lokal kerap kali dinarasikan sebagai kaum yang marjinal, kurang intelektual, kelas perekonomian menengah kebawah dan stereotip negatif lainya yang beredar di masyarakat yang multikultur. Menggunakan metode tipologi dalam perancangan, untuk merubah dan menciptakan persepsi dan narasi baru tentang Betawi. Mengadaptasi dari perspektif arsitektur, kebiasaan, dan juga keseharian dari adat Betawi, lalu diterjemahkan menjadi sebuah bentuk dan ruang yang berbeda tetapi mengandung unsur yang sama. Mentransformasikan bentuk baru dari rumah adat Betawi, dengan cara merekronstruksi ulang setiap elemen-elemen terkait, dari aspek struktur, ornamen, filosofi, dsb. Proyek ini bertujuan untuk merubah stereotip/pandangan dari orang-orang terhadap Betawi dan menciptakan paradigma dan stigma baru terhadap komunitas Betawi. Dengan mengangkat permasalahan yang dihadapi secara riil yaitu ekonomi dan juga krisis identitas, maka diusung untuk merancang fasilitas yang dapat mewadahi produktivitas dan disisi lain mempromosikan budaya Betawi itu sendiri.